Mental Health Evaluation As A Preventive Measure For Student Academic Disorders - Fatmah Bagis; Efi Miftah Faridli; Uswatun Hasanah (EDUCATION JOURNAL OF INDONESIA, 2025)
Mental health in Indonesia has become a serious focus of attention in recent years with the highest cases of depressive disorders, namely 9,162,886 cases or 3.7% of the population. This study aims to provide insight into mental health problems faced by first and second year students, offering guidance and research to address this issue in educational settings. The study employs a longitudinal research method to evaluate the impact of mental health on new students in 2023, utilizing quantitative data analysis and statistical analysis. Students participated in a mental health survey using the WHOQOL-BREF instrument as a questionnaire. This study revealed that students initially experienced mental and physical stress due to their adaptation and response to the new system and climate, which potentially affected their performance in education. New students experienced a boost in social relationships due to numerous friends and support from both material and non-material sources. The majority of new students at Islamic Universities come from the same province, causing an increase in the adjustment of the living environment.